Robotic mitral valve repair surgery: where do we go from here? - Tomšič, Anton; Palmen, Meindert (Frontiers in Cardiovascular Medicine, 2023)
Surgical mitral valve repair through median sternotomy has long presented the treatment of choice for degenerative mitral valve disease. In recent decades, minimal invasive surgical techniques have been developed and are gaining widespread popularity. Robotic cardiac surgery presents an emerging field, initially adopted only by selected centres, mostly in the United States. In recent years, the number of centers interested in robotic mitral valve surgery has grown with an increasing adoption in Europe as well. Increasing interest and surgical experience gained are stimulating further developments in the field and the full potential of robotic mitral valve surgery remains to be developed.